2020
DOI: 10.15632/jtam-pl/115550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the parameters of a vehicle crashing into a round pillar

Abstract: This article presents a study on reconstruction of a crash of a passenger car-Opel Mokka, into a pillar. Computer simulations were performed with software V-SIM4, both for default data and data identified from the crash test. The crash test was performed by AUTOBILD and DEKRA. The frontal collision with a pillar is not a standard crash test recommended by the Directives of CommunautéÉconomique Européenne (CEE), even though this type of collision poses a serious threat to the safety of vehicle users. The threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Secondly, for the drivers and passengers, the operating standards in the process of work are unreasonable. Some drivers do not conduct the "five-step brake" test on the brakes before starting work, resulting in a serious shortage of pressure holding time [20]. When the main and auxiliary drivers monitor the data, there is no double-checking mechanism, so inconsistent data often appears on the display, which will cause the GYK monitoring device to open abnormally.…”
Section: The Management Of the Team Of Drivers And Passengers Needs T...mentioning
confidence: 99%
“…Secondly, for the drivers and passengers, the operating standards in the process of work are unreasonable. Some drivers do not conduct the "five-step brake" test on the brakes before starting work, resulting in a serious shortage of pressure holding time [20]. When the main and auxiliary drivers monitor the data, there is no double-checking mechanism, so inconsistent data often appears on the display, which will cause the GYK monitoring device to open abnormally.…”
Section: The Management Of the Team Of Drivers And Passengers Needs T...mentioning
confidence: 99%
“…The mass and the moment of inertia of the carrying structure of the flat wagon with the design parameters and with the actual parameters were determined through their spatial models in SolidWorks software [10][11][12] The mass of the carrying structure of the flat wagon with the design parameters was 15.6 tons, the moment of inertia 283.1 ton × m 2 , and those with the actual parameters 11.1 ton and 102 ton × m 2 , respectively (Figure 5). Differential Equations ( 1)-( 6) were reduced to standard Cauchy problems and then they were integrated by the Runge-Kutta method [13][14][15][16][17][18]. The initial displacements and speeds were taken equal to zero.…”
Section: The Presentation Of the Main Content Of The Studymentioning
confidence: 99%
“…Differential Equations ( 1)-( 6) were reduced to standard Cauchy problems and then they were integrated by the Runge-Kutta method [13][14][15][16][17][18]. The initial displacements and speeds were taken equal to zero.…”
Section: The Presentation Of the Main Content Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…V-SIM, however, has not been verified with a full-frontal rigid barrier impact test. In other studies [8,9], contact parameters and other data were identified from crash tests and used in simulation. The articles present both the results of computer simulation of a passenger cars crash with a non-deforming barrier and a pole with V-SIM and the experimental results published by Allgemeiner Deutscher Automobil-Club and AUTOBILD.…”
Section: Introductionmentioning
confidence: 99%